2008
DOI: 10.1364/ol.33.002011
|View full text |Cite
|
Sign up to set email alerts
|

Optical poling in germanium-doped microstructured optical fiber for visible supercontinuum generation

Abstract: We report visible supercontinuum generation initiated by the second harmonic generation obtained in a germanium-doped microstructured optical fiber after optical poling processing. The visible spectral broadening is due to a cross-phase modulation effect between the generated IR solitons and the second harmonic (532 nm) of the 1064 nm pump wave. The 400-650 nm white-light emission is obtained on the fundamental propagation mode of the fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…7, we may notice that in the former case the visible region of the SC spectrum is significantly enhanced by broadband XPM among wavelengths situated on opposite sides of the ZDW (so that they travel at the same group velocity). Such interaction leads to asymmetric spectral broadening, as it was also pointed out in previous works [2,14,[20][21][22]. We also studied the impact on SC broadening of varying the input pump power by gradually changing the intensity of the pump beam through an optical attenuator.…”
Section: Continuum Generation In the Central Coresupporting
confidence: 53%
“…7, we may notice that in the former case the visible region of the SC spectrum is significantly enhanced by broadband XPM among wavelengths situated on opposite sides of the ZDW (so that they travel at the same group velocity). Such interaction leads to asymmetric spectral broadening, as it was also pointed out in previous works [2,14,[20][21][22]. We also studied the impact on SC broadening of varying the input pump power by gradually changing the intensity of the pump beam through an optical attenuator.…”
Section: Continuum Generation In the Central Coresupporting
confidence: 53%
“…Over the past few decades, optical fibres featuring various materials and geometries have been investigated for improving the nonlinear coefficient n 2 , effective mode area size A eff , and dispersion distribution. The synergetic effect of highly nonlinear materials and photonic crystal structures (e.g., germanium-doped silica cores789, zirconium-fluoride-based fibres1011, and chalcogenide glasses fibres12) have maximized the nonlinear performance, which has led to spectra broadening ranging from deep UV to mid-IR. Recently, CMOS-compatible broadband light sources based on silicon (Si) and silicon nitride (Si 3 N 4 ) have emerged because these materials can be monolithically integrated with electrical circuits by using the nanometers-scale process rule.…”
mentioning
confidence: 99%
“…In that way, a significant visible spectrum enlargement can be obtained for any value of the secondharmonic (SH) power, even weak, its spectral width being determined by the IR radiations velocities. It was also demonstrated that the dual pumping process writes a permanent grating in the germanium-doped fiber, so that efficient broadband SHG can be obtained directly from the poled fiber when using the IR pump only [38]. Recent experiments have investigated the limitations due to the Raman effect in the self-poling process occurring in a germanium-doped standard single-mode fiber [39].…”
Section: Visible Supercontinuum In Optically Poled Pcfsmentioning
confidence: 99%